Pemanfaatan Media Sosial Untuk Pemasaran Produk Pada UMKM Kelurahan Meteseh Kecamatan Tembalang - Emaya Kurniawati; Adijati Utaminingsih; Widjaksono R Hartoto (CV. Multi Kreasi Media, 2024)
The Community Service activities that we carry out at the Joint Jaya Lestari UMKM Business Group in Meteseh Subdistrict, Tembalang District, Semarang City, where business actors or members of Jaya Lestasi UMKM have not been able to market and sell their products widely using social media. So far, it has only been marketed to nearby areas and close friends or relatives. With the existing problems, this community service activity provides training on using social media to market and introduce products online, so that it can increase sales and income for Jaya Lestari MSME members. product marketing and also provides practice on how to make product photos so they are attractive to consumers.